THE CHEMOADJUVANT POTENTIAL OF PERGULARIA DAEMIA (FORSK.) ON EXPRESSION PATTERN IN EXPERIMENTAL ORAL CARCINOGENESIS - Mirunalini, Sankaran; Karthishwaran, Kandhan; Vaithiyanathan, Velusamy (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Abstract Pergularia daemia (Family: Asclepiadaceae), is a perennial herb growing widely along the road sides of India. Traditionally, the plant is utilized in many disease conditions. These findings provide valuable information that might help in the selection of possible biomarkers that can be used in early detection of the alarming problem of oral cancer in Southeast Asia. Topical application of DMBA for 14 weeks induced buccal pouch tumours that showed aberrant expression of cytokeratins, a marker for epithelial carcinomas. This was associated with increased cell proliferation and evasion of apoptosis as revealed by upregulation of proliferating cell nuclear antigen, NF-ÎºB, mutant p53, Bcl-2 and downregulation of Bax and caspase 3 protein expression. Our findings clearly suggest that PDME may play a role as a novel chemopreventive or therapeutic agent for oral carcinogenesis. Key words: Pergularia daemia, Chemoadjuvant, RT-PCR, Western Blotting